Unilateral and equitransitive tilings by squares of four sizes - Mann, Casey (Ars mathematica contemporanea, 2016)
D. Schattschneider proved that there are exactly eight unilateral and equitransitive tilings of the plane by squares of three distinct sizes. This article extends Schattschneider's methods to determine a classification of all such tilings by squares of four different sizes. It is determined that there are exactly 39 unilateral and equitransitive tilings by squares of four different sizes.
Keywords: ekvitranzitiven; equitransitive; kvadrati; squares; tilings; tlakovanja; unilateral; unilateralen